Characterization of Fibrillization Process of Amyloid-Beta on Lipid Membrane Utilizing a Cantilever-Based Liposome Biosensor. (2015) - Zhang, Z.; Sohgawa, M.; Yamashita, K.; Noda, M.
Abstract: We have developed a strain-gauge cantilever-based biosensor with liposomes as model cell membrane immobilized on the cantilever surface to investigate time course of dynamic behavior of amyloid-beta (1-40) protein (Aβ(1-40)) on lipid membrane. The results of this work clearly exhibit the characteristic of chronological change of the gauge resistance, which is closely related to the dependence of Aβ-liposome interaction extent on the state of Aβ during fibrillization and the type of lipid molecule. Therefore, it is considered that these results can adequately reflect the fibrillization process of Aβ(1-40) on different kinds of lipid membranes. Meanwhile, it means that we are able to discriminate the molecular states of Aβ and evaluate Aβ fibrillization process using the cantilever-based liposome biosensor.